Evaluación de la adición de levadura de cerveza (Saccharomyces cerevisiae) en la alimentación de cuyes (Cavia porcellus) en la etapa de crecimiento y engorde en el barrio Alpamala de Acurio del cantón Pujilì - Chicaiza Sarzosa, Luis Miguel (2015)
This research was conducted in Alpamala of Acurioneigborhood, located in Pujilí canton, Cotopaxi province, for a period of eight weeks. The aim of the research was to assess three levels of beer yeast (1, 2, 3%) in the feeding of guinea pigs in the stage of growth and fattening. 40 male guinea pigs of 17-days-old of age were selected. 4 groups of 10 animals selected randomly were formed. The experimental group received a phase of adaptation of 15 days and they were weighted weekly. Gathering the results of each treatment, it is concluded that the T3 (S. cerevisiae 3% alfalfa) reached a final average weight of 917, 9 g, followed by the T2 (S. cerevisiae 2% + alfalfa) that reached a final average weight of 932, 1 g, and the T1 (S. cerevisiae 1% + alfalfa) reached a final average weight of 811, 4 g. The less efficient was the T4 (Alfalfa) that reached a final average weight of 729, 5 g. In feed conversion, the best treatment was the T2 (S. cerevisiae 2% alfalfa) with 3.25 g during the trial taking into account that in other treatments there is not a very high contrast since with the T3 there is a difference of 0. 07g....